Is There a Right Time to Know? The Right Not to Know and Genetic Testing in Children. Issue 1 (28th April 2014) - Borry, Pascal; Shabani, Mahsa; Howard, Heidi Carmen
Abstract : The increasing implementation of next‐generation sequencing technologies in the clinical context and the expanding commercial offer of genetic tests directly‐toconsumers has increased the availability of previously inaccessible genetic information. A particular concern in both situations is how the volume of novel information will affect the processing of genetic and genomic information from minors. For minors, it is argued that in the provision of genetic testing, their "right not to know" should be respected as much as possible. Testing a minor early in life eliminates the possibility for the minor to make use of his or her "right not to know." The article discusses the theoretical underpinnings of the right not know, analyzes reasons why various direct‐to‐consumer companies process samples from minors, and discusses the right not to know in relation to common complex disorders in a pediatric population.